Interpretation : - Nolan, James (Multilingual Matters, 2005)
This book provides a structured syllabus and an overview of interpretation accompanied by exercises in the main aspects of the art. It is meant as a practical guide for interpreters and as a complement to interpreter training programmes, particularly for students preparing for conference interpreting in international governmental and business settings.